A new dawn for the international tax system : evolution from past to future and what role will China play? - Turley, Conrad; Chamberlain, David (Tax advisor); Petriccione, Mario (IBFD, 2017)
The global tax system is currently in a period of flux, with the BEPS Project driving a significant overhaul of international tax rules. At the same time, China's growing economic sophistication has prompted radical change in Chinese cross-border tax rules and a shift in China's engagement with global tax rule-setting bodies. This book provides a long-run perspective on the development of the global taxation framework and analyses China's rules against developments elsewhere in the world.